Commitment based human resources practices and knowledge creation in ambidextrous organizations: A moderated mediation study on expatriates working in India. (20th July 2022) - Nayak, Sunanda; Bhatnagar, Jyotsna; Budhwar, Pawan; Mukherjee, Jaydeep
Abstract: Through the lens of organizational learning theory, we develop and test a moderated mediation model of commitment‐based HR practices (CBHRP), absorptive capacity, organization structure and routines, and knowledge creation in ambidextrous organizations. We test two new individual‐level dimensions of absorptive capacity (AC) in ambidextrous organizations: ambidexterity and flow experience. This empirical investigation is based on 377 expatriates who responded to our survey over two time periods working in various multinational organizations' R&D centers in India. Our findings suggest that CBHRP is critical in predicting knowledge creation and AC in an ambidextrous organizational context. Furthermore, we find that AC mediates the linkage between CBHRP and knowledge creation, and organization structure and routines (OSR) act as a moderator. Focusing on expatriates in ambidextrous organizations, our study extends contextual understanding of ambidextrous organizations and integrates organizational learning and knowledge creation theory into strategic human resources management (SHRM) research.